2009
DOI: 10.1007/s00299-009-0677-3
|View full text |Cite
|
Sign up to set email alerts
|

Twinned microspore-derived embryos of canola (Brassica napus L.) are genetically identical

Abstract: Microspore culture is used extensively in several crop species to generate diverse populations of homozygous, doubled haploid lines for breeding and genetic analyses. In our canola (Brassica napus L.) doubled haploid breeding programme we regularly observe conjoined microspore-derived embryos, most commonly twins, joined either at the base of the hypocotyl or along the length of the hypocotyl axis. The aim of this study was to determine if twinned embryos were genetically identical or non-identical in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Two pairs of twins were observed from marker results. These plants may have resulted from secondary embryogenesis generating identically twinned embryos during the tissue culture process (Raemakers et al 1995;Cousin and Nelson 2009); one of each pair was removed from the analysis. Of the remaining 84 individuals, 75 (89%) were heterozygous at 38-86% (average 68%) of loci in the A genome; heterozygosity was assessed as presence of both a B. juncea and a B. napus parental allele at a single A-genome locus (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two pairs of twins were observed from marker results. These plants may have resulted from secondary embryogenesis generating identically twinned embryos during the tissue culture process (Raemakers et al 1995;Cousin and Nelson 2009); one of each pair was removed from the analysis. Of the remaining 84 individuals, 75 (89%) were heterozygous at 38-86% (average 68%) of loci in the A genome; heterozygosity was assessed as presence of both a B. juncea and a B. napus parental allele at a single A-genome locus (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 57 microspore-derived plants in 10 progeny sets with nonidentical haplotypes in Mason et al (2011a), an additional eight individuals were conservatively excluded for this study after SNP marker genotyping revealed that they may have been clones (.95% similar genetic identity) (Raemakers et al 1995;Cousin and Nelson 2009) (Table S1). An additional four clone pairs were also identified in the new microspore-derived progeny, and one of each pair was excluded from further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The mapping population (LMDH) used in this study was a doubled haploid (DH) B. napus population (n = 131) derived from reciprocal F1 hybrids created from two genetically-distinct parents (European summer annual-type ‘Lynx-037DH’ and an Australian summer annual-type ‘Monty-028DH’ [32], [33]) using the method described by Cousin and Nelson [34]. The parents were homozygous DH lines developed by microspore culture from the varieties ‘Lynx’ and ‘Monty’, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, parent genotypes were derived from a process of doubled-haploidy through microspore culture protocols described in Nelson et al (2009) [19] and Cousin and Nelson (2009) [39] and bulked by pure seed methods. The five B. napus genotypes were "Surpass400_024DH", "Trilogy", "Westar_010DH", "Monty_028DH" and "Boomer", and are hereafter referred to as N1, N2, N3, N4 and N5, respectively.…”
Section: Methodsmentioning
confidence: 99%